Detection of Asymptomatic Sickle Cell Hemoglobin Carriers and Fetal Hemoglobin Regulating Genetic Variants in African Descendants from Oaxaca, Mexico - María De Los Ángeles Romero-Tlalolini; Sergio Roberto Aguilar-Ruiz; Rafael Baltiérrez-Hoyos; Jaime Vargas-Arzola; Luis Alberto Hernández-Osorio; Verónica Rocío Vásquez-Garzón; Héctor Ulises Bernardino-Hernández; Honorio Torres-Aguilar (Anemia)
Sickle cell anemia has been classified as a noninfectious neglected tropical disease and, although not exclusively, affects African descendants more frequently. This study aimed to detect asymptomatic sickle cell hemoglobin carriers (HbAS) in marginalized and vulnerable populations during a public health screening in African descendants from Oaxaca, Mexico, and to validate an amplification refractory mutation system (ARMS)-PCR methodology to detect fetal-hemoglobin (HbF)-regulating genetic variants in BCL11A toward affordable routine association of single nucleotide variants (SNVs) with HbF concentrations. To this aim, hemoglobin variants were detected by acidic citrate agar and alkaline cellulose acetate electrophoreses. SNVs in the hemoglobin subunit beta gene (HBB) were identified by the β-globin mutation detection assay (β-GMDA) and ARMS-PCR, respectively, and validated by Sanger sequencing. The association between genotypes and HbF concentrations was evaluated using Spearman’s correlation coefficient. The results obtained during a directed screening in 140 self-identified African descendants revealed 42 HbS-carriers (30%), of which 39 showed normal total hemoglobin concentrations (92.8%), only 3 presented anemia (7.2%), and 9 showed quantifiable HbF concentration (21.4%). As validated by Sanger sequencing, the designed ARMS-PCR efficiently detected homozygous and heterozygous variants in BCL11A. In a cohort of 42 heterozygous (HbAS) and 27 healthy (HbAA) individuals from the same population, only one SNV (rs766432) showed statistically significant association with increasing HbF concentration, and two new unrelated homozygous silent variants were identified. This study reveals the need to raise coverage of HbS screening in vulnerable populations and shows a feasible low-cost ARMS-PCR methodology to determine the presence of SNVs in quantitative trait loci affecting HbF.